Community-acquired vancomycin-resistant Enterococcus faecium: a case report from Malaysia - Raja, N.S.; Karunakaran, R.; Ngeow, Y.F.; Awang, R. (Microbiology Society, 2005)
Vancomycin-resistant enterococci (VRE) are formidable organisms renowned for their ability to cause infections with limited treatment options and their potential for transferring resistance genes to other Gram-positive bacteria. Usually associated with nosocomial infections, VRE are rarely reported as a cause of community-acquired infection. Presented here is a case of community-acquired infection due to vancomycin-resistant Enterococcus faecium. The patient had been applying herbal leaves topically to his cheek to treat a buccal space abscess, resulting in a burn of the overlying skin. From pus aspirated via the skin a pure culture of E. faecium was grown that was resistant to vancomycin with a MIC of >256 microg ml-1 by the E test and resistant to teicoplanin by disc diffusion, consistent with the VanA phenotype. The organism was suspected of contaminating the leaf and infecting the patient via the burnt skin. This case highlights the need for further studies on the community prevalence of VRE among humans and animals to define unrecognized silent reservoirs for VRE, which may pose a threat to public health.